Combustion temperatures and nutrient transfers when grasstrees burn - Wittkuhn, R.; Lamont, Byron; He, Tianhua (Elsevier, 2017)
Fire controls the structure and functioning of many ecosystems, especially through its effects on biomass and nutrient cycling. Fire mineralizes soil nutrients and returns plant-locked nutrients to the soil. Nutrients are also lost from the ecosystem through release of particulates and volatile compounds during the fire, and later through surface transport and leaching when it rains. Xanthorrhoea preissii is the dominant grasstree in fire-prone southwestern Australia. Dead leaves are retained on the plant as a ‘skirt’ that envelopes the trunk. This makes the plants highly combustible and provides a unique opportunity to investigate burn temperatures and subsequent nutrient transfers to the soil and atmosphere. Temperatures of combustion and nutrient dynamics were determined for grasstrees in two vegetation types (woodland and forest) and at two fuel ages (5 and 15 years postfire). During fire, dead leaves burnt at up to 1020 °C (mean 496 ± 240 °C) and living leaves up to 740 °C (mean 257 ± 218 °C), whereas the tightly packed juvenile leaves 15 cm above the apical meristem only reached 85 °C (mean 44 ± 20 °C). Dead leaves stored more nutrients than living, except for P and K that were leached out over time. Ash deposits were highest for B (37–52% of prefire mass), Mg (30–50%), Na (26–45%), Ca (36–44%), P (28–41%) and K (18–30%). Biomass and N deposits in ash were <2% of prefire values. Atmospheric export of N and S during fire ranged 67–82% of prefire mass (5-year sites) and 82–95% (15-year sites), mainly as a result of volatilization. Losses of K (4–55%), Mg (47–59%), Ca (39–61%), B (31–59%), and Na (35–69%) were likely to be via particulates. Loss of P (10–46%) was likely to be from a combination of particulates and volatiles, and was greater from the older fuel ages. In conclusion, the foliage of grasstrees is a significant repository of mineral nutrients and is almost completely incinerated by fire. Nevertheless, grasstrees are able to recover from fire as the apical meristem is well-protected from the heat. Less than half the store of nutrients is usually returned to the soil while more than half may be transferred to the atmosphere, representing a major source of nutrient loss from fire-impacted ecosystems. Longer intervals between fires may result in greater export of P from ecosystems already low in available P when fire does occur. The disparate effects of different fire intervals on ecosystem nutrient dynamics needs to be recognized in management of fire-prone vegetation.